Check list of hover flies (Diptera, Syrphidae) of west part of Zarafshan mountain ridge - Rakhimov, Mukhammadtuychi R. (Acta Biologica Sibirica, 2023)
The article, based on materials from the author’s collections for 2017−2022 and partly on the collections of the Samarkand State University (Samarkand) and the Samarkand Museum of Local Lore, provides the first data on the distribution of 79 species of syrphids from 3 subfamilies in the Western part of the Zarafshan ridge. Ten species have been recorded for the first time in Uzbekistan: Chrysotoxum kirghizorum Peck, 1974, Eupeodes asiaticus (Peck, 1972), Scaeva dignota (Rondani, 1857), Syrphus rectus Osten Sacken, 1875, Xanthogramma hissarica Violovitsh, 1975, Chrysogaster cemiteriorum (Linnaeus, 1758), Cheilosia aerea Dufour, 1848, Ch. lola Zimina, 1970, Ch. stackelbergi Barkalov & Peck, 1994, and Volucella bella Barkalov, 2003. In addition, one genus – Neocnemodon Goffe, 1944 recorded for the first time for Uzbekistan.